Baduy People of Banten Disagree with Some Accounts of Researchers: A Comparative Text Analysis - Cleghorn, William; Isnendes, Retty (Lexeme : Journal of Linguistics and Applied Linguistics, 2025)
The Baduy people, a tribal group from Banten, Indonesia, are known for their self-isolation, environmental care, and resistance to change. With a cultural aversion to writing, they rely on oral traditions to preserve their history and beliefs. Concerns over misrepresentation in research publications led the Baduy elders to authorize Saatnya Baduy Bicara (SBB), the first official book presenting their viewpoints. This study uses comparative text analysis to examine SBB alongside external research publications, focusing on conflicting statements regarding the Baduy people’s origin and preferred titles. Five variables are analyzed to assess the credibility of statements from both sources. The findings show that the Baduy elders demonstrate strong internal consistency and source perspective, reflecting their cultural and ideological coherence. However, their weaknesses in methodology, data collection, and external validation are attributed to their cultural rejection of writing. Conversely, external researchers excel in methodology, data collection, and intent/purpose but lack source perspective and often present limited or biased theories. The results emphasize the need to address cultural and methodological biases to ensure balanced and accurate interpretations of indigenous knowledge systems. By bridging gaps between oral traditions and academic research, a more credible and inclusive understanding of the Baduy people can be achieved.